Interrelation of the type of higher nervous activity with the working capacity of sports horses of the jumping group - Петрушко, М. П.; Кабасова, І. О. (Scientific Progress & Innovations, 2018)
In this work, studies have been carried out on the relationship between the type of higher nervous activity (GNI) of horses and their shown working capacity during participation in competitions to overcome obstacles. The research was conducted on 10 heads of horses of the jumping group of the Dergachevska children's and youth horse riding school, who had experience of participating in competitions to overcome obstacles. It is established that the most promising for use in the competition are horses of strong, balanced mobile type of GNI; The horses of strong balanced inert type of GNI are suitable for participation in competitions under the beginning riders and as hobby-class horses; horses of a strong unbalanced type of GNI have unrealized sports potential and need a training system that is aimed not only at developing physical qualities, but also to increase stress resistance in competition conditions.